Differentiated Learning for Disabilities in Inclusive Class : Learning Groups On Inclusive Class By Using Multiple Strategies - Elma Nur Hafizah; Noor Alfulaila (INCLUSIVE EDUCATION, 2023)
The inclusive education is an innovation where there are no boundaries for everyone in getting education. But there were some problem, students with special needs still left behind by the others. In this case teacher also having a difficult position, one side they want to achieve the goals but on the other side, they have to teach and learn new thing at the same time to guide student with special needs on their learning process. This research held by using descriptive qualitative approach through interview, observation, documentation and systematic literature review, on this topic through google search engine and field observation we collected data through semi-structured interviews and descriptive observations to teachers and selected students at SDIT Al Firdaus. The results highlight that there are some ways on learning groups that can be applied on inclusive class through multiple strategies that will fit each student’s needs by making learning groups.